Graphical models for security : 5th International Workshop, GraMSec 2018, Oxford, UK, July 8, 2018, Revised selected papers /: 5th International Workshop, GraMSec 2018, Oxford, UK, July 8, 2018, Revised selected papers. (2019) - Unknown
No abstract available